TROPIS, the tree growth and permanent plot information system - Vanclay, J.K. (1997)
TROPIS, the Tree Growth and Permanent Plot Information System, contains five elements: (1) a network of people willing to share permanent plot data and tree growth information (serviced by newsletters and information sources hosted at http://www.cifor.id/tropis or available form CIFOR), (2) an index to, or metadatabase of, people and institutions holding permanent plot data, (3) a database management system (MIRA) to assist more efficient data management, (4) a system (WORLD) to identify comparable sites in other regions, allowing data from elsewhere to be used when no local growth information exists, and (5) an inference system (PLANTGRO) to allow growth estimates to be made in the absence of empirical data. Most of these components are still under development, but the first two elements are operational. The index or metadatabase currently contains references to 10 000 plots with 2 000 species contributed by 100 collaborators, and is growing at about 1 000 plots per month. Searches of the database are welcomed, and may be directed to the author.